2020
DOI: 10.4047/jap.2020.12.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Fitting accuracy of ceramic veneered Co-Cr crowns produced by different manufacturing processes

Abstract: PURPOSE. The purpose of this in vitro study was to evaluate the fitting accuracy of single crowns made from a novel presintered Co-Cr alloy prepared with a computer-aided design and computer-aided manufacturing (CAD/ CAM) technique, as compared with crowns manufactured by other digital and the conventional casting technique. Additionally, the influence of oxide layer on the fitting accuracy of specimens was tested. MATERIALS AND METHODS. A total of 40 test specimens made from Co-Cr alloy were investigated acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, clinical and in vitro studies on MC crowns have shown satisfactory results for marginal adaptation. [52][53][54][55] The limitations of the study include a lack of comparison with conventional impressions and that it was conducted in an institutional environment. Therefore, further long-term RCTs considering these aspects are needed to confirm the present results.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical and in vitro studies on MC crowns have shown satisfactory results for marginal adaptation. [52][53][54][55] The limitations of the study include a lack of comparison with conventional impressions and that it was conducted in an institutional environment. Therefore, further long-term RCTs considering these aspects are needed to confirm the present results.…”
Section: Discussionmentioning
confidence: 99%
“…The gap space is a determining factor for the longterm integration and failure of a restoration 27,28 . It is critical for tooth and periodontal health to reduce marginal and internal fit inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…The vitro study was conducted at the department of Prosthodontics, Hainan Stomatological Hospital, China, from October 2021 to March 2022, and this study was approved by the Ethics Review Committee of Hainan Stomatological Hospital, China. The sample size was calculated on the basis of literature [10][11][12] . The sample comprised patients undergoing implant surgery on maxillary or mandibular first molars, with normal gap, occlusal space >6.0mm, normal bone morphology and no requirement of bone augmentation surgery.…”
Section: Methodsmentioning
confidence: 99%